2000
DOI: 10.1111/1468-2362.00056
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Euro's Progress

Abstract: The evolution of the euro since its inception has appeared inexplicable. This paper develops a monetary model of the euro/US dollar exchange rate to track the progress of the currency, both before and after Stage 3 EMU. The relationship between the exchange rate, money stocks, GDP, interest and inflation rates, and prices is identified. The observed patterns of behaviour during the 1990s are used to predict the euro's value up to mid-2000; a consistent finding is that the euro is over-predicted by 23-30%. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This result is in line with some recent findings by Andersen et al (2003) and Conrad et al (2002). Fourth, there is considerable time variation, revealing interesting 1 See, for example, Alberola et al (1999), Borowski and Couharde (2000), Chinn and Alquist (2000), Clostermann and Schnatz (2000) and Duval (2000). These studies generally found that the euro was undervalued, but the results vary substantially.…”
Section: Introductionsupporting
confidence: 86%
“…This result is in line with some recent findings by Andersen et al (2003) and Conrad et al (2002). Fourth, there is considerable time variation, revealing interesting 1 See, for example, Alberola et al (1999), Borowski and Couharde (2000), Chinn and Alquist (2000), Clostermann and Schnatz (2000) and Duval (2000). These studies generally found that the euro was undervalued, but the results vary substantially.…”
Section: Introductionsupporting
confidence: 86%
“…There is ample interest in the post-1999 behaviour of the euro, particularly its initial depreciation and subsequent sharp appreciation, which provided the basis for previous studies, as in Nautz and Offermans (2006), Heaney and Pattenden (2005), Mussa (2005), Schnatz et al (2004), and Chinn and Alquist (2000). Second, we examine the relative performance of a model incorporating a role for net foreign assets, as suggested in Gourinchas and Rey's (2005) financial adjustment channel and Lane and Milesi-Ferretti (forthcoming).…”
Section: Introductionmentioning
confidence: 94%
“…It follows that in addition to monetary aggregates and base money, further determinants of the exchange rate are factors that influence the demand for money such as income, interest rates and inflation rate. Monetary models for the euro/dollar exchange rate have been developed and estimated by Chinn and Alquist (2002) and van Aarle et al (2000).…”
Section: Other Than Natrexmentioning
confidence: 99%